Aktywność mniejszości niemieckiej w Polsce w życiu politycznym na poziomie centralnym na przykładzie kampanii wyborczej 2019 roku - Nijakowski, Lech M. (Rocznik Polsko-Niemiecki, 2020)
This article analyses the manner in which the German minority in the Opole region, whose members belong to the Social-Cultural Society of Germans in Opole Silesia, participates in Poland’s political life, using the example of the 2019 national election campaign. The campaign has shown that the German minority in the Opole region, in fact, forms an ethnic political party. The old dichotomy between symbolic politics (the reproduction of identity) and the pursuit of common interests is no longer valid. The German minority strives to achieve both these objectives. German minority organisations may be viewed as sectional interest groups.